Confusion and Slurred Speech in a 34-Year-Old Woman from India - Chugh, Chandril; Biller, Jose (Frontiers in Neurology, 2011)
A 34-year-old woman from India, presented with episodes of confusion and progressive speech deterioration. She also had a painless neck “lump”, which persisted despite antibiotics. She was diagnosed to have a space occupying lesion in the left parietal lobe, which was subsequently biopsied.